Mapping the Evolution of Leadership in Sports Coaching: A Bibliometric Review - Primadi, Zahra Naqiyyah; Fitri, Mustika; Saputra, Yudha Munajat; Apriady, Hilmy (Journal of Sport Science and Fitness, 2024)
Leadership in sports coaching plays a crucial role in enhancing athlete performance and team well-being. This study aims to identify key themes in sports coaching leadership usingbibliometric analysis supported by VOSviewer software. The analysis results reveal eight main clusters, including athlete leadership, motivational climate, team cohesion, and athletes' mentalhealth. Each cluster highlights the strong relationship between coaching leadership styles and athletes' experiences and performance. Leadership styles such as transformational leadership and servant leadership have been found to contribute positively to athletes' motivation, satisfaction, and mental well-being, whereas unsupportive approaches are oftenassociated with burnout. Additionally, the bibliometric analysis identifies the significant contributions of leading authors and countries such as the United Kingdom and the United States inthis research field. This study emphasizes the importance of a holistic leadership approach that focuses not only on technical strategies but also on athletes' psychological well-being to achieve optimal performance.